Muslims and the Making of Modern Europe - Greble, Emily, 1978- (New York: Oxford University Press, 2021)
"Muslims have lived in Europe for hundreds of years. Only in 1878, however, did many of them become formal citizens of European states. Muslims and the Making of Europe shows how this massive shift in citizenship rights transformed both Muslims' daily lives and European laws and societies. Starting with the Treaty of Berlin and ending with the eradication of the Shari'a legal system in Communist Yugoslavia, this book centers Muslim voices and perspectives in an analysis of the twists and turns of nineteenth and twentieth century European history, from early nation-building projects to the shattering of the European imperial order after World War I, through the interwar political experiments of liberal democracy and authoritarianism, and into the Second World War, when Muslims, like other Europeans, were caught between occupation and civil conflict, and the ideological programs of fascism and communism. Its focus moves from "Ottoman Europe" in the late nineteenth century to Yugoslavia, a multi-confessional, multi-lingual state founded after World War I. Throughout these decades, Muslims negotiated with state authorities over the boundaries of Islamic law, the nature of religious freedom, and the meaning of minority rights. As they did so, Muslims helped to shape emergent political, social, and legal projects in Europe"--
1. Muslim rights and political belonging after the Congress of Berlin --2. Confessional sovereignty and the formation of a Muslim legal other -- 3. Survival and autonomy : lessons of the Balkan Wars and the First World War -- 4. Second- or third- class citizens : becoming minorities after World War I --5. The Shari'a mandate and Yugoslav nation-building -- 6. "The bonfire of Muslim unity" : Muslim politics and the crisis of Yugoslav democracy -- 7. Islamic legal revivalism and the crisis of Europe --8. "Back to Islam!" : the promise and possibility of Hitler's Europe --9. The eradication of the Shari'a legal order in Tito's Yugoslavia.
Includes bibliographical references (pages 321-335) and index.
Keywords: Muslims -- Europe -- History -- 20th century; 19th century; Legal status, laws, etc; Civil rights; Freedom of religion; Religion and politics